The ‘‘inclusive volunteering’’ phenomenon: Research into the volunteering of people with disabilities - Marková, Aneta (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2018)
Social settings have recently undergone significant changes. The dynamics of society are increasing, as is the pressure of the changes in the skills and abilities needed for its good functioning. However, changes associated with this development may cause problems to those whose health is disadvantageous in terms of acquiring the necessary skills. For this reason, it is necessary to seek and find ways to eliminate the problems associated with the increasing societal pressure. Research on volunteering benefits shows that volunteering can play a significant role in the process of education and the subsequent involvement of people with disabilities in the new socio-cultural environment. Taking this into consideration, in recent years the term "inclusive volunteering" has emerged to support the efforts of society to achieve inclusion. This article introduces the inclusive volunteering that has recently emerged in research by experts in various social sciences. The main section of the article details the realization and results of the survey called "volunteering of people with disabilities", conducted by the author. The final discussion provides a comparison of the paper's revelations with existing literature.
Fenomén inkluzivní dobrovolnictví: Výzkum dobrovolnické činnosti osob s postižením
Keywords: Volunteering; Inclusive volunteering; People with disabilities; Grounded theory; Social role; Dobrovolnictví; inkluzivní dobrovolnictví; osoby s postižením; zakotvená teorie; sociální role